Identification of Human Pathogen in Nutrient Culture Media using an Electronic Nose - Zulkifli, Syahida Amani; Mohamad, Che Wan Sharifah Robiah; Abdullah, Abu Hassan (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper present human pathogen bacteria for early screening using electronic nose. An electronic nose (Enose) designed for mimicking the mammalian olfactory system to recognize gases and odors. Electronic nose used for detecting different bacteria such as Pseudomonas aeruginosa and Shigella cultured on media agar. In addition, the data from the electronic nose (E-nose) is processed using a statistical method which is principal component analysis (PCA) and existing classification method which is K-Nearest Neighbor Method (KNN). The study shows the capability of electronic nose (E-nose) for early screening for bacterial infection in the human stomach.